Jysk ordbog på nettet - Arboe, Torben (Nordiske Studier i Leksikografi, 2003)
The Dictionary of the Jutland Dialects has recently been transfered to the Internet as far as the editing has been completed, i.e. A-Gn until now. The paper first describes the facilities of the dictionary’s homepage (fig. 1): the background material and the structure of the entries can be studied via the links of the left column, and after having downloaded the dictionary’s special font through a link from the center column the user may start searching for entries of interest. With the entry of brænde (i.e. burn) as a starting point (fig. 2) the links from the editorial text to maps of pronunciation etc. and to the register of sources are demonstrated (section 2), supported by the entry of brække (i.e. break) as to maps of word and meaning distribution (fig. 3). Some problems of the necessary text-internal references and the making of thousands of links to represent them are discussed (section 3). Lists of users’ searches for entries are used for further discussion of links needed (section 4). In summarizing, an overview of the types of links is given (fig. 4, section 5). Aspects regarding the users by the transition from an ‘ordinary’ to an Internet dictionary are briefly considered (section 6).